Implementasi Etnomatematika Pada Pembelajaran Matematika Di SMP Negeri 7 Kotamobagu - Nurul Halima Dwi Putri; Anetha L. F. Tilaar; Santje M. Salajang (Lembaga Pengembangan Kinerja Dosen, 2022)
Mathematics is often seen as a deductive science and is not related to social aspects. Even though mathematics grows and develops from socio-cultural practices that occur in society. This is the basis for the development of ethnomathematics concepts. The ethnomathematics concepts in the Bolaang Mongondow community are very diverse. This study aims to describe the implementation of ethnomathematics in learning mathematics at SMP Negeri 7 Kotamobagu, especially in the use of regional languages ​​and symbols of the Bolaang Mongondow Kabela Box Craft. The data obtained is in the form of qualitative data while the sources are obtained from interviews, observation, and documentation from informants (teachers, students and craftsmen). The main instrument is the researcher, while the supporting instruments used are interview guides and documentation. The results showed that the regional language and the symbols of the Bolaang Mongondow Kabela Box craft really helped teachers and students in the process of learning mathematics at SMP Negeri 7 Kotamobagu.